New Trends in Amplifiers and Sources via Chalcogenide Photonic Crystal Fibers - L. Mescia; F. Smektala; F. Prudenzano (International Journal of Optics)
Rare-earth-doped chalcogenide glass fiber lasers and amplifiers have great applicative potential in many fields since they are key elements in the near and medium-infrared (mid-IR) wavelength range. In this paper, a review, even if not exhaustive, on amplification and lasing obtained by employing rare-earth-doped chalcogenide photonic crystal fibers is reported. Materials, devices, and feasible applications in the mid-IR are briefly mentioned.